1985
DOI: 10.1148/radiology.155.2.3983401
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunodetection of melanoma utilizing In-111 96.5 monoclonal antibody: a preliminary report.

Abstract: The murine 96.5 monoclonal antimelanoma antibody (MoAb) was labeled with In-111, and 1-20 mg were administered to 21 patients who had proved or suspected melanoma metastases. One patient was studied twice. In four patients, unlabeled 96.5 MoAb was administered prior to the radiopharmaceutical. All of the patients tolerated the procedure without toxicity regardless of the mass of MoAb administered. The scans were interpreted by two observers, one with full knowledge, the other with no knowledge of the cases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…This finding contrasts with those of previous studies where it was concluded that administration of cold antibody was beneficial. The earlier studies, however, claimed an improvement only in the number of tumour deposits localised in patients with multiple tumours and have not demonstrated increased tumour uptake of radioactivity (Halpern et al, 1985;Murray et al, 1985;Carrasquillo et al, 1986).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding contrasts with those of previous studies where it was concluded that administration of cold antibody was beneficial. The earlier studies, however, claimed an improvement only in the number of tumour deposits localised in patients with multiple tumours and have not demonstrated increased tumour uptake of radioactivity (Halpern et al, 1985;Murray et al, 1985;Carrasquillo et al, 1986).…”
Section: Discussionmentioning
confidence: 98%
“…Although it has been suggested by some authors that the presence of antigen in the blood does not significantly affect the results of imaging (Goldenberg et of tumour sites detected on immunoscintigraphy is increased (Halpern et al, 1985;Murray et al, 1985;Carrasquillo et al, 1986). This conflict of opinion on the significant of circulating immune complexes may be explained by differences in the antigen associated with the tumour and those present in the circulation and also in their affinity of binding to administered radiolabelled antibody.…”
Section: Discussionmentioning
confidence: 99%
“…When "'In-labeled antibodies have been injected into patients, however, a very high nonspecific uptake has always been observed in the reticuloendothelium, especially in the liver (26,38), even when the DTPA coupling was performed under mild conditions (25,39). Since high nonspecific liver uptake may interfere with the detection of liver metastases, we considered this label not to be optimal for the evaluation of colon carcinoma patients by immunoscintigraphy.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute tumour antibody uptake has been determined with a range of values reported, from 0.001% injected dose (ID)/gram tissue (Armitage et al 1984;Halpern et al 1985;Halpern and Dillman 1987;Carrasquillo et al 1988) to 0.007%ID/g (Armitage et al 1985;Davidson et al 1989). The lowest value, 0.001%ID/g, was adopted as a worst-case study, with normal tissue activity concentration set at a level of 0.0005%ID/g to be consistent with this at the lowest turnout to normal tissue ratio of 2:1.…”
Section: Phantom Modelmentioning
confidence: 99%